AIM2 Inflammasome-Mediated Pyroptosis in Enterovirus A71-Infected Neuronal Cells Restricts Viral Replication - Yogarajah, T.; Ong, Kien Chai; Perera, D.; Wong, Kum Thong (Nature Publishing Group, 2017)
Encephalomyelitis is a well-known complication of hand, foot, and mouth disease (HFMD) due to Enterovirus 71 (EV71) infection. Viral RNA/antigens could be detected in the central nervous system (CNS) neurons in fatal encephalomyelitis but the mechanisms of neuronal cell death is not clearly understood. We investigated the role of absent in melanoma 2 (AIM2) inflammasome in neuronal cell death, and its relationship to viral replication. Our transcriptomic analysis, RT-qPCR, Western blot, immunofluorescence and flow cytometry studies consistently showed AIM2 gene up-regulation and protein expression in EV-A71-infected SK-N-SH cells. Downstream AIM2-induced genes, CARD16, caspase-1 and IL-1β were also up-regulated and caspase-1 was activated to form cleaved caspase-1 p20 subunits. As evidenced by 7-AAD positivity, pyroptosis was confirmed in infected cells. Overall, these findings have a strong correlation with decreases in viral titers, copy numbers and proteins, and reduced proportions of infected cells. AIM2 and viral antigens were detected by immunohistochemistry in infected neurons in inflamed areas of the CNS in EV-A71 encephalomyelitis. In infected AIM2-knockdown cells, AIM2 and related downstream gene expressions, and pyroptosis were suppressed, resulting in significantly increased virus infection. These results support the notion that AIM2 inflammasome-mediated pyroptosis is an important mechanism of neuronal cell death and it could play an important role in limiting EV-A71 replication.